Targeting Trimethylamine N-Oxide: A New Therapeutic Strategy for Alleviating Atherosclerosis - Jing, Lele; Zhang, Honghong; Xiang, Qiannan; Shen, Liang; Guo, Xiaoxia; Zhai, Changlin; Hu, Huilin (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis is one of the most common cardiovascular diseases, there is currently no effective drug to reverse its pathogenesis. Trimethylamine N-oxide (TMAO) is one of the metabolites of gut flora and may act as a new risk factor for cardiovascular disease. Many studies have shown that TMAO is involved in the occurrence and development of atherosclerotic diseases through various mechanisms, but the targeted therapy for TMAO is still controversial. This article summarizes the important progress of TMAO and atherosclerosis in recent years, and provides new ideas for the prevention and treatment of atherosclerosis.